The correlation between demographic characteristics and mental health in victims of rape referred to Isfahan province forensic medicine center in year 2015 - khademi, Nasim; Nahidi, Fatemeh (Advances in Nursing & Midwifery, 2017)
Abstract Background and Aim: sexual assault is one of the most important factors posing a serious threat to the health and rights of women in the word. However, factors that affected on the health of victims are less-known. This study aimed to determine the relationship between demographic characteristics and mental health of the victims in the year 2013. Materials & Methods: This was a descriptive study, which was carried out in 2013. The sample size was 93 people who were randomly selected from rape victims in the Isfahan forensic medicine center. Measuring tools was demographic characteristic’s questionnaire and 90 item- symptom revised checklist (SCL90-R). The data were analyzed by descriptive statistics and spearman’s correlation, Independent t-test and one-way ANOVA test using SPSS 16. Findings: Spearman’s correlation test between demographic characteristics and mental health score indicates that factors, including age of victim (p=0.99) and income of victim (p=0.08) did not have a significant relationship with the mental health score. The relationship between victim’s father education (p=0.008) and mental health was significant. The victims who had fathers with a diploma degree significantly had higher mental health scores than those who were their fathers had lower education. Conclusion: The majority of the victims had a mental disorder with high or very high degree of severity. Most seen symptoms were depression and aggressive behaviors. For the prevention of psychological consequences of rape, the family and social networks should enforce to identify and treat victims who have suffered trauma.